Antimicrobial Sensitivity Pattern of Bacterial Isolates from Patients with Urinary Tract Infection in Kishoreganj District, Bangladesh (Community Based Medical Journal, 2025)
Urinary tract infections (UTIs) are a major public health concern in terms of morbidity and financial implications. A cross-sectional, descriptive study was conducted on 728 patients with urinary tract infection (UTI) in President Abdul Hamid Medical College & Hospital, Kishoreganj, Bangladesh, between September 2021 and August 2023. Clean-catch midstream urine specimens from the patients were inoculated on blood agar, McConkey Agar and chromogenic agar plates, which were incubated aerobically at 37ºC overnight. Plates with colony count exceeding 105cfu/ml were subjected for identification.  Antimicrobial sensitivity was tested using Kirby Bauer disc diffusion method. Of 728 urine samples, 210 (28.85%) had growth with urinary pathogens. The prevalence of UTI was high among females than males. Females of the reproductive age group (21-50years) constituted 60.9% of the total patients with UTI. However, the youngest age group (1-10 years) and elderly (51-70 years) males had a higher incidence of UTI (51.6% and 22.6% respectively) compared to the youngest and elderly females (10.1% and 7.2% respectively). The commonest isolates were E. coli (73%) and Enterococci (22%). E. coli showed high sensitivity to amikacin (86.9%) and gentamicin (72.5%) meanwhile Enterococci are highly sensitive to amikacin (76.6%), gentamicin (74.5%), ciprofloxacin (68.1%). To address the emerging challenges posed by E. coli, gentamicin, nitrofurantoin and imipenem are also effective options in addition to amikacin.CBMJ 2025 July: vol. 14 no. 02 P:187-192